LAGU POP BALI DALAM PELESTARIAN BUDAYA BALI - I Nyoman Mardika; I Dewa Putu Sumantra (Kulturistik: Jurnal Ilmu Bahasa dan Budaya, 2020)
Balinese Pop Songs is an important media to help preserve Balinese culture, especially the Balinese language. In addition to the Balinese language is now increasingly less attractive to the younger generation of the main generation who were eroded by the development of globalization due to the increase in technological development. As a media, Balinese Pop Songs have been developing since the 1970s are now facing challenges in the development of the music world. Because, on the other hand, Balinese pop songs are expected to continue to exist, while on the other side, they are expected to help preserve Balinese culture. The concept of preservation published here is through the Balinese pop song Balinese language which is increasingly marginalized due to the insistence of globalization. The Balinese language which is the basis for Balinese pop songs must remain a prominent feature even though sometimes there must be Indonesian, regional and foreign languages as interludes. The use of Balinese language which dominates is certainly directly to invite listeners or viewers to participate in preserving the use of Balinese language. Balinese language as part of Balinese culture must be able to face the development of the dynamics Balinese culture.